Perancangan Media Pembelajaran Berbasis Video Animasi pada Materi WAN Kelas XI SMKN 1 Wakatobi: Design of Animated Video-Based Learning Media for WAN Material for Class XI of SMKN 1 Wakatobi - La Ode Muhammad Arif Dirmansyah; Darman Darman; Alfiah Fajriani (ITScience (Information Technology and Science), 2025)
This study aims to design and develop animated video-based learning media for Wide Area Network (WAN) subjects for 11th-grade students of Computer and Network Engineering at SMKN 1 Wakatobi. The development was carried out using the ADDIE model, which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. This study uses a Research and Development (R&D) approach involving material experts, media experts, and students as respondents. The data collection process was carried out through observation, interviews, and validation questionnaires. The validation results showed that the developed media obtained an average score of 83% with a very valid category. Material experts received the highest score of 88%, while media experts scored 75%. Student responses reached 93%, with a very valid category. The implementation of media in learning showed an increase in student learning outcomes, from an average of 63.2% in the pre-test to 93% in the post-test, after using animated videos. The N-gain calculation of 0.64 indicates moderate effectiveness, meaning this media has a positive impact on improving the understanding of WAN concepts. In addition to improving learning outcomes, animated videos have also been shown to foster motivation, capture attention, and create interactive and enjoyable learning experiences. Therefore, this animated video-based learning medium is deemed suitable for use as an innovative and relevant digital learning tool to support learning in 21st-century vocational high schools.